2013
DOI: 10.3892/mmr.2013.1503
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody preparation of Golgi phosphoprotein 2 and preliminary application in the early diagnosis of hepatocellular carcinoma

Abstract: Golgi phosphoprotein 2 (Golph2) is a type II Golgi‑specific membrane protein, which has been found to be overexpressed in hepatocellular carcinoma (HCC) patients. The sensitivity of diagnosis of HCC using Golph2 (76%) was markedly elevated compared with alpha‑fetoprotein (AFP) (70%), and Golph2 is expected to be a novel and effective serum biomarker for the diagnosis of HCC. The aim of this study was to prepare monoclonal antibodies against Golph2 and to establish double-antibody sandwich enzyme-linked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[28] Therefore, an additional marker, such as SOD, has been suggested to be simultaneously measured to improve the HCC detection rate. This study showed a significant increase in serum AFP in HCC patients compared to HBV patients without HCC and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Therefore, an additional marker, such as SOD, has been suggested to be simultaneously measured to improve the HCC detection rate. This study showed a significant increase in serum AFP in HCC patients compared to HBV patients without HCC and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques of GOLPH2 quantification have evolved in recent years from time-consuming Western Blotting (WB) [11]. via Enzyme linked Immuno Sorband Assays (ELISA) [11][12][13][14][15] to particle based unpretentious bioassays. Quantification of GOLPH2 expression in tumour tissue by immunohistochemistry (IHC), a routine clinical technique, paved the way for exploration of GOLPH2 expression in solid tumours like HCC, prostate [16] and gastric cancer [17], lung adeno carcinoma [18,19], glioblastoma [20] and melanoma [21].…”
Section: Golph2 a Biomarker For Malignant Diseasesmentioning
confidence: 99%
“…Ju et al found that a type II Golgi-specific membrane protein, Golgi phosphoprotein 2, was overexpressed in HCC patients and it was more sensitive for diagnosis of HCC (76%) than the traditional biomarker AFP (70%). 11 Therefore, Golgi phosphoprotein 2 may be a new and effective serum biomarker for HCC diagnosis. Youns et at described that talin-1 has the potential to serve as an important prognostic marker for the diagnosis of HCC, with superior sensitivity and specificity when compared to AFP.…”
Section: Diagnosismentioning
confidence: 99%